LONG TERM CONSEQUENCES OF PRECOCIOUS PUBERTY - EXPLORING HEALTH, METABOLIC, AND PSYCHIATRIC CHALLENGES - Justyna Popczyńska; Agnieszka Raczyńska; Natalia Pacocha; Oliwia Krzemień; Kinga Kosiec; Jakub Jędrychowski; Natalia Karpowicz; Julia Kaszucka; Małgorzata Krzyżanowska; Marta Zgierska (International Journal of Innovative Technologies in Social Science, 2024)
Introduction and objective: Precocious puberty (PP) is a condition marked by the premature onset of puberty in children, which can lead to a range of physical, metabolic, and psychological challenges. This review seeks to assess the health implications of precocious puberty and evaluate the treatment options available, with particular emphasis on GnRH analog therapy and the psychological support required for both affected children and their families. Review methods: A comprehensive review of studies related to precocious puberty was conducted, focusing on its physical, metabolic, and psychological effects. Research was analyzed on how PP impacts growth, obesity risk, insulin resistance, cardiovascular diseases, and emotional and social challenges in affected children. Results: The findings suggest that precocious puberty leads to reduced final height, an increased risk of obesity, insulin resistance, and cardiovascular diseases. Additionally, girls with precocious puberty are at higher risk for developing polycystic ovary syndrome (PCOS), mood disorders, body image issues, and social challenges. GnRH analog therapy has been shown to improve growth outcomes, though the effectiveness of treatment varies depending on the age of initiation and the progression of puberty. Conclusion: Precocious puberty is associated with a range of serious health consequences that require a comprehensive treatment approach. Successful management should not only address the medical aspects but also incorporate psychological support and emotional monitoring to improve the overall well-being and quality of life. Early intervention and parental education are essential for improving outcomes, and further research is needed to refine treatment strategies and better understand the long-term effects of this condition.